Effect of two different doses of dexmedetomidine on the incidence of emergence agitation after strabismus surgery: a randomized clinical trial - Abdel-Rahman,Khaled Abdel-Baky (2018)
Abstract Background and objective: Emergence agitation is a postoperative negative behavior that affects mainly children. We studied the effect of two different doses of dexmedetomidine on the incidence and degree of EA in children undergoing strabismus surgery. Methods: 90 patients were allocated into three equal groups; patients received 0.5 µg.kg−1 of dexmedetomidine in high Dex group, 0.25 µg.kg−1 of dexmedetomidine in low Dex group, or normal saline in the placebo group. All drugs were received with the closure of the conjunctiva before the end of the surgery. Pediatric Anesthesia Emergence Delirium (PAED) scale was used to evaluate the agitation, and Face, Legs, Activity, Cry, Consolability (FLACC) scale was used for pain assessment. Adverse effects of dexmedetomidine and recovery times were recorded. Results: The incidence of agitation was significantly lower in high Dex group compared to other groups and it was significantly lower in low Dex group compared to placebo group. The median (range) of FLACC score was significantly lower in both Dex groups compared to placebo group. Recovery times; time from removal of laryngeal mask to eye opening and time stay in post anesthesia care unit was significantly longer in high Dex group compared to other groups. No significant bradycardia or hypotension was recorded. Recovery time was significantly longer in high Dex group compared to the other two groups. Conclusion: Dexmedetomidine (0.5 µg.kg−1) before emergence from general anesthesia resulted in a reduction in the incidence of emergence agitation compared to a dexmedetomidine (0.25 µg.kg−1) but on the expense of recovery times without adverse effects.